2018
DOI: 10.15253/2175-6783.20181933961
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s satisfaction with nursing care on the post-surgery of radical prostatectomy

Abstract: Objetivo: avaliar a satisfação do paciente e suas experiências vivenciadas com o cuidado de enfermagem no pós-operatório de prostatectomia radical aberta. Métodos: estudo transversal, realizado com 60 pacientes. Foram utilizados ficha de caracterização pessoal e clínica dos sujeitos e a versão brasileira do instrumento Newcastle Satisfaction with Nursing Scales. Realizada análise descritiva dos dados e de correlação das características dos pacientes com escores de satisfação e experiência do paciente. Resultad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Thus, satisfaction is considered an important indicator of health service quality and the nursing team needs more and more to have knowledge of the factors that impact the perception of the patient about the care offered. 2 The performance of the nurse is important to improve satisfaction because by reconfiguring the care directed to the user, it can lead to the production of an assistance where the desires of the user are noted beyond the purely biological needs. 3 The aim is excellence of care, through the provision of health services that can meet the needs and desires, attracting and faithfulness to all users, whether visitors, patients or companions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, satisfaction is considered an important indicator of health service quality and the nursing team needs more and more to have knowledge of the factors that impact the perception of the patient about the care offered. 2 The performance of the nurse is important to improve satisfaction because by reconfiguring the care directed to the user, it can lead to the production of an assistance where the desires of the user are noted beyond the purely biological needs. 3 The aim is excellence of care, through the provision of health services that can meet the needs and desires, attracting and faithfulness to all users, whether visitors, patients or companions.…”
Section: Introductionmentioning
confidence: 99%
“…Ozsaker et al [32] reported in their study that the care for privacy was a condition that created high satisfaction in surgical patients. Marcelina et al [33] found that patients who undergoing radical prostatectomy were highly satisfied with their privacy. In the study conducted by Yanmıs [34] it was highly welcomed that nurses were aware of the requirements of urology patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the information passed to a patient and their families, in an intensive care unit, after elective cardiac surgery, was related to higher satisfaction with nursing care [37]. The research among patients after radical prostatectomy showed that positive experience and satisfaction might be linked to the educational role of nursing staff, their communicational skills, and respect for privacy [38].…”
Section: Experience and Satisfaction With Nursing Care Vs Sociodemogr...mentioning
confidence: 97%